2002
DOI: 10.2134/jeq2002.2058
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Characteristics of Dairy Feces Affected by Diets

Abstract: Phosphorus (P) surplus on dairy farms, especially confined operations, contributes to P buildup in soils with increased potential for P loss to waters. One approach to reduce P surplus and improve water quality is to optimize P feeding and improve P balance on farms. Here we report how varying P concentrations in lactating cow diets affects the amount as well as the chemical forms and fraction distribution of P in fecal excretion, and the environmental implications of this effect. Analysis of fecal samples col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
78
2
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 24 publications
7
78
2
2
Order By: Relevance
“…When the mean values of individual cow data at three different stages during the LP were used, TP and SP showed the same pattern (Figure 1). The results of the present study therefore indicate that TP or SP can be used to identify cows overfed with P. Since any surplus P consumed is almost entirely excreted as SP (Dou et al, 2002), it would probably be more appropriate to use SP as the indicator of P overfeeding. However, when it comes to the assessment of P overfeeding on farms under practical conditions, TP may be a more attractive alternative since the cost of analysis is lower and additional data, for example on other minerals, can be obtained through combined analysis.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…When the mean values of individual cow data at three different stages during the LP were used, TP and SP showed the same pattern (Figure 1). The results of the present study therefore indicate that TP or SP can be used to identify cows overfed with P. Since any surplus P consumed is almost entirely excreted as SP (Dou et al, 2002), it would probably be more appropriate to use SP as the indicator of P overfeeding. However, when it comes to the assessment of P overfeeding on farms under practical conditions, TP may be a more attractive alternative since the cost of analysis is lower and additional data, for example on other minerals, can be obtained through combined analysis.…”
Section: Discussionmentioning
confidence: 69%
“…In contrast to many other species, for example pigs, adult ruminants normally excrete excess P in faeces, while only trace amounts of P are excreted in urine (Valk et al, 2000). When potentially absorbable P is provided in sufficient amounts or in excess, dairy cows have a profound ability to excrete the P surplus with faeces, largely as water-soluble inorganic P (Dou et al, 2002;Ekelund et al, 2005). This fraction can serve as an indicator of excessive P feeding on farms (Dou et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, reducing the P content of dairy cow rations to the extent adopted within the current experiment has the potential to have a significant impact on farm P balances, and thus the likelihood of P loss to the environment. In addition, Dou et al (2002) observed an increased proportion of water soluble P in the faeces of cows offered high P diets, while Ebeling et al (2002) showed that P runoff from slurry produced from cows offered a high P diet was considerably greater than for slurry produced by cows offered a low P diet.…”
Section: Cow Fertilitymentioning
confidence: 97%
“…Furthermore, livestock utilize P inefficiently, excreting 60 to 80% of what they consume (Knowlton et al 2004). It has been shown that nearly all of the excess dietary P above the animal's requirement is excreted in the faeces (Dou et al 2002) suggesting that the optimal strategy to reduce P excretion is to develop diets that closely match the animal's P requirements. In the Netherlands, the excretion of P per grower-finisher pig has been more than halved in the past 30 yr by reducing the amount of P fed and by genetic improvement (Jongbloed and Valk 2004).…”
mentioning
confidence: 99%
“…Powell et al (2001) estimated that crop acreage required to recycle faecal P was decreased by 39% when dietary P was reduced from 0.48 to 0.38% P on a DM basis. Increasing dietary P levels using mineral P not only led to a higher concentration of total faecal P, it also increased water soluble P, which is most susceptible to loss in the environment (Dou et al 2002). Several studies have assessed the effects of dietary P levels 20 to 25% below NRC (2001) requirements and reported little negative impact on dry matter intake (DMI), milk production, health or reproductive performance of dairy cows (Valk and Sebek 1999;Knowlton and Herbein 2002;Valk et al 2002).…”
mentioning
confidence: 99%